Predicting the need for ventilatory support in organophosphorous compound poisoning - Philip, Sudha Mary (International Journal of Research in Medical Sciences, 2018)
Background: Organophosphorus compound poisoning is one of the most common poisonings often requiring ICU care and ventilatory support. Hence this study was undertaken to identify the factors, which predict the need for ventilation in these patients. Methods: All the patients who were diagnosed to have consumed organophosphorus compound poison admitted in RLJ Hospital and SNR District Hospital Kolar, Karnataka, India who presented within 24hours of consumption were included in the study. Patients with concomitant respiratory illness, double poisoning and those treated outside were excluded from the study. Results: A total number of 50 patients were studied. 30(60%) were males and 20 (40%) were females. 18 patients required ventilation. 100% of patients with respiratory rate>25 breaths/minute and 55% of patients with a fasciculation score of >4 required ventilation. Ventilation was required by 84.6% of patients who has a GCS Score of <10. 21.7% of patients with mild and 33.3% with moderate poisoning required ventilation. In contrast 66.6% of patients with severe poisoning required ventilation. Of the patients admitted to the hospital >4hours after consumption of poison, 36% required ventilation. Of the 19 patients who had oxygen saturation levels <89%, 18 patients (94.7%) required ventilation. Patients who were ventilated required a higher dose of atropine within 48hours of admission as compared to those who were not ventilated. Conclusions: Patients who presented with higher respiratory rate, accessory muscles of respiration in action, higher fasciculation score, GCS score of 10, greater lag time between consumption of poison and admission to hospital (4hours), severe grade of poisoning and O2 saturation <89% were more likely to require ventilation. There is no relationship between the age group, sex, pulse rate, pupil size and type of organophosphorous compound consumed with the need for ventilation.